2012
DOI: 10.1007/s11670-012-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1, E-cadherin and β-catenin in gastric carcinoma, precancerous tissues and chronic non-atrophic gastritis

Abstract: Objective: To investigate the expressions of caveolin-1, E-cadherin and β-catenin in gastric carcinoma, precancerous gastric and chronic non-atrophic gastritis tissues, and evaluate the correlation of these expressions with the development of gastric cancer.Methods: The expressions of caveolin-1, E-cadherin and β-catenin were detected by biotin-streptavidinperoxidase (SP) immunohistochemistry on 58 gastric cancer tissues, 40 precancerous gastric tissues and 42 chronic non-atrophic gastritis tissues. The correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
2
22
2
Order By: Relevance
“…Though Cav-1 over-expression was documented to associate with Lymph node metastasis and TNM stage (Sun et al, 2012;Nam et al, 2013), here our results suggested that Cav-1 positive expression was not correlated with these clinicopathological features.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Though Cav-1 over-expression was documented to associate with Lymph node metastasis and TNM stage (Sun et al, 2012;Nam et al, 2013), here our results suggested that Cav-1 positive expression was not correlated with these clinicopathological features.…”
Section: Discussioncontrasting
confidence: 79%
“…Indeed, even if it may play a role of tumor suppressor by inhibiting the signalling transduction products of some proto-oncogenes (Razani et al, 2001), its tyrosine-14 phosphorylation leads to growth stimulation (Lee et al, 2000), demonstrating that Cav-1 may also make an effect as a pro-tumorigenic factor. In the prognosis of gastric cancer, it has been reported that Cav-1 expression may serve as a promising molecular biomarker recently (Gao et al, 2005;Barresi et al, 2008;He et al, 2012;Sun et al, 2012;Nam et al, 2013;Zhao et al, 2013). However, these results were controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way we constructed the TMAs and the microarray system instrument were the same with our previous study [24], [25]. As previously studies did not report intratumoral heterogeneity of Cav-1 expression in GC and our feasibility experiment indicated that one core per tumor on TMA and large sections showed a good consistency [26], [27], [28], therefore, in testing experiment, one core was sampled in each case. Briefly, one core with a diameter of 1.5 mm was taken from each sample and inserted into empty “recipient” paraffin blocks; these blocks were cut into sections (4 µm thick) and used for QDs-IHC analysis.…”
Section: Methodsmentioning
confidence: 93%
“…In a study by Sun et al [26], Cav-1 expression was evaluated in 5 gastric cancer tissues, 40 precancerous gastric tissues (19 intestinal metaplasia and 21 dysplasia), and 42 nonatrophic gastritis tissues. They showed that Cav-1 positivity was significantly lower in the gastric cancer tissues compared to precancerous gastric and non-atrophic gastritis tissues [26]. Moreover, different from our study, low Cav-1 expression was found to be significantly correlated with lymph node metastasis and advanced pTNM stage.…”
Section: Discussionmentioning
confidence: 99%